2022
DOI: 10.1159/000524414
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Pharmacological Intervention of Endothelial Progenitor Cells in the Treatment of Ischemic Stroke

Abstract: <b><i>Background:</i></b> Ischemic stroke, a common central nervous system disease that seriously threatens human life and health, is characterized by rapid progress and a high disability fatality rate. Ischemic tissue can produce a large amount of vascular endothelial growth factor (VEGF) and stromal cell-derived factor 1 (SDF-1) to promote the mobilization of endothelial progenitor cells (EPCs). <b><i>Summary:</i></b> As newly discovered stem cells, EPCs can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…EPC, a precursor of vascular EC, can be obtained from circulating monocyte populations, umbilical cord blood, and BM. 53 , 54 It was found that when vessels are exposed to ischemia and hypoxia, perfusion of BM-derived EPC enables them to migrate to the ischemic region and differentiate into mature vascular EC to repair damaged vessels and promote new vessel formation, or secrete cytokines, including VEGF and basic fibroblast growth factor, to indirectly participate in vascular remodeling. 55 , 56 …”
Section: Bbb Repair Therapiesmentioning
confidence: 99%
“…EPC, a precursor of vascular EC, can be obtained from circulating monocyte populations, umbilical cord blood, and BM. 53 , 54 It was found that when vessels are exposed to ischemia and hypoxia, perfusion of BM-derived EPC enables them to migrate to the ischemic region and differentiate into mature vascular EC to repair damaged vessels and promote new vessel formation, or secrete cytokines, including VEGF and basic fibroblast growth factor, to indirectly participate in vascular remodeling. 55 , 56 …”
Section: Bbb Repair Therapiesmentioning
confidence: 99%